Law Enforcement Based on the Age of Thinking (Mesu Budi): Beyond Call for Duty - Sigit Sapto Nugroho; Taufiq Yuli Purnama; Bambang Sukarjono; Yuni Purwati (Universitas Muhammadiyah Surakarta, 2023)
This article aims to develop a model of thinking for law enforcement officials with a model of thinking that enters the dimension of depth, namely looking for hidden meanings and values in the object being examined through sharp thinking (mesu budi) or using spiritual intelligence. Spiritual intelligence does not want to be limited by benchmarks, nor is it only contextual, but wants to get out of the existing situation in an effort to find deeper truths, meanings or values. The sharpness of thinking (mesu budi) is a concretization of the transcendental approach in law enforcement and is interesting to be linked to ways of thinking in law, which in turn affects one's actions in carrying out the law, especially judges in court. The interaction between law combined with spiritual values in the context of law enforcement is very important, which includes: ethics, morals and religion. In the end, spiritual thinking or spiritual intelligence as a concretization of the transcendental approach becomes an offer or formulation and even an antithesis of a non-systematic and positivistic-legalistic paradigm or approach, in the context of law enforcement to dig deeper (dive to depth / think falsafati), there will be found divine values, human values, justice values, and the value of benefits.